Budget implementation performance indicators and the government's internal control system on performance accountability of government agencies - Adikusumah, Kreshna; Akhmadi, Akhmadi; Ichwanudin, Wawan (Institute of Computer Science (IOCS), 2023)
This research uses a value for money concept approach to determine the influence of Budget Implementation Performance Indicators and the Government's Internal Control System on Performance Accountability of Government Agencies. The sample used was a Work Unit within the scope of the National Population and Family Planning Agency during the 2019-2022 fiscal year period. Data processing was carried out using the STATA Version 14.2 application. The results of the research show that statistically it is not proven that the Budget Implementation Performance Indicators have an effect on the Performance Accountability of Government Agencies, the Government Internal Control System is proven to have an effect on the Performance Accountability of Government Agencies, the Budget Implementation Performance Indicators and the Government Internal Control System are simultaneously proven to have an effect on the Performance Accountability of Government Agencies . These findings reinforce that if improvements in Budget Implementation Performance Indicators and the Government's Internal Control System are carried out simultaneously, it will improve the quality of budgeting which is economical, effective, efficient and will increase the Performance Accountability of Government Agencies in line with the concept of value for money